Textiles From Our Place: Exploring Connective Textile Making as a Phenomenology of Locale - Donovan, Joanne Mary (Auckland University of Technology, 2022)
This doctoral research queries the question; what is the process, outcome, and experience of crafted textile making, springing from a locally generated self-reliance? The thesis gives focus to a process of making that forms through the maker’s locale, which is relied upon for salvaged materials, impressions, memories, and experiences to activate the making process. The approach is introspective and localized, with emphasis placed on what the human being can do and achieve, within their singular sphere of experience. Drawing upon local self-reliant traditions encountered as a child in Aotearoa New Zealand, the practice explores locally available materials using improvisation as a design method. The locale is treated dialogically, from where materials and the environs are responded to as a way to generate an idiosyncratic textile vernacular. Collaging, juxtaposition, felting, and stitch are developed as methods to explore materials and the research question within a materials-led design process. Fibres and fabrics are layered to communicate narratives, memories, and experiences drawn from the materials and therefore, from the locale. The textiles appear multi-vocal as layers of context are blended using stitch and felt. Through making, the textiles are experienced as linked to place while also connecting temporally through stories and traces of previous touch to a journey through time. Textiles in this research shift from temporary and brief to perceived within a material continuum that is always evolving and devolving. The research is situated between craft and design, as maker-led, materials-led practice. Drawing on sources from anthropology, and philosophy along with craft and design theory, the creative practice inquiry, investigates textile as matter in motion, making as journeying within a locale and through the experiences of the maker.
Keywords: Textile design; Practice-led research; Craft; Materiality; Locale; Vernacular making; Materials-led practice; Maker-led research; Improvisation; Salvage and reuse; Felting; Stitch; Design anthropology; Craft philosophy; Self-reliance; Aotearoa New Zealand; Sense of place; Tactility; Embodied knowledge